Development of Self-Adaptive PVD Coatings for Machining TI6Al4V Alloy - Chowdhury, Mohammad (My University, 2021)
The usage of titanium alloys in many industries has increased significantly over the years due to their superior properties. However, they are extremely difficult to machine because of their distinctive characteristics such as their high temperature strength, low thermal conductivity, and high chemical affinity for tool materials. Hence, despite their increased usage, they are still expensive to machine when compared to other metals. The current research aims to address the machinability issues of titanium alloys by developing novel compositions of a new generation of self-adaptive Physical Vapor Deposition (PVD) coatings that function by forming beneficial tribo-films through their interaction with the environment. These tribo-films form during cutting and provide enhanced lubricity, hardness, strength, and thermal barrier characteristics to the cutting tool. It was found that during Ti6Al4V machining, significant BUE and crater wear formation occurs; however, one is dominant over the other depending on the cutting conditions. Therefore, the coatings investigated were designed by taking into consideration the dominant tool wear mechanisms and the complex tribological phenomena that occur in the cutting zone. The current research investigated monolayer TiB2 and CrN self-adaptive PVD coatings for the rough (cutting speed - 45 m/min, feed -0.15 mm/rev, and depth of cut – 2 mm) and finish (cutting speed - 150 m/min, feed -0.1225 mm/rev, and depth of cut – 0.25 mm) turning of Ti6Al4V alloy. Detailed experimental studies were performed to study the effectiveness of the coatings during machining. Micro-mechanical characteristics of the coatings were also studied to understand how coating properties affect the coatings performance in machining and tribo-film formation. The results obtained show that both the TiB2 and CrN coatings significantly improve tool performance during the rough turning of Ti6Al4V alloy compared to the current industrial standard, which is due to certain micro-mechanical coating properties and the beneficial tribo-films formed. A coating of CrN coating was found to increase tool life during finish turning. It was also established that for machining applications where intensive adhesive interaction occurs at the tool-chip interface, coatings with lower hardness values perform significantly better than harder ones.
Keywords: Rough turning, finish turning, Ti6Al4V alloy, PVD coating, built up edge (BUE), flank wear, crater wear, tribo-films.